Obtenção e seleção de populações de tomateiro anão do tipo saladete para o desenvolvimento de linhas de introgressão - Oliveira, Camila Soares de (2023)
The use of dwarf tomato strains to obtain hybrids can be an excellent alternative to increase productivity in tomato plants. However, there are still no introgression strains with this technology for saladette-type tomato. Through the backcrossing method, populations of dwarf tomato are obtained, and from the characterization and study of genetic dissimilarity between populations, it is possible to select the most promising ones for the development of lineages. Therefore, the objective of this work was to obtain populations of saladette-type dwarf tomato using the backcrossing method, and to select those with better agronomic potential, higher fruit quality and broad spectrum of pest resistance for the development of introgression lines. The work was carried out in three stages: characterization of dwarf tomato populations obtained after backcrossing (F2RC1); evaluation of the potential and genetic dissimilarity of dwarf populations obtained after self fecundation (F3RC1) and characterization of dwarf tomato populations obtained after the first (RC1) and second backcrossing (RC2), with the objective of verifying the increments provided in each backcrossing, as well as selecting the best genotypes for the development of introgression lines. Both experiments were conducted in a greenhouse at the Vegetable Experiment Station of the Federal University of Uberlândia (UFU), Monte Carmelo-MG. Dwarf tomato populations were characterized for agronomic potential, fruit quality, and pest resistance. The data were analyzed using test of means, multivariate analysis, and selection indices. In the first experiment it was found that the first backcrossing provided increased fruit size in the tomato populations, and the UFU SDi 7, UFU SDi 9 and UFU-SDi 17 populations were selected by two selection indices. In the second experiment it was found that the Kohonen map was more coherent in distinguishing the genetic dissimilarity between the F3RC1 tomato populations. In the third experiment, the populations : UFU_13_1, UFU_SDi _17_1, UFU_10_1, UFU_11_3, UFU_10_3 and UFU _11_2 from the second backcross were considered promising for the development of introgression lines.